The power of creative intelligence : 10 ways to tap into your creative genius - Buzan, Tony. (London Bloombury, 2001)
10 ways to tap into your creative genius Did you know the number of ideas it is possible for your brain to create is greater than the number of atoms in the known universe? Creativity is not just painting a picture or playing an instrument - it can be part of every decision you take! This book is full of fun games and tools to help you make the most of your own creativity. When you are creative, you are full of energy, enthusiasm, and ideas. Using the famous Mind Map techniques that he invented, Tony Buzan shows you how to learn from geniuses like Leonardo Da Vinci and the Beatles, so you can be: * Fluent - develop the speed and ease with which you come up with new and creative ideas. * Flexible - your ability to see things from different angles, including your ability to use all your senses in the creation of new ideas. * Original - At the heart of creative thinking, lies your power to produce ideas that are both unique and unusual. * Expansive - develop your ideas and push them to their limits. So go on - take a break from the norm!